The Impact of Ecotourism Expansion on Biodiversity Conservation and Indigenous Cultural Heritage in Fiji - Prasad, Ravinesh Rohit; Kumar, Shivneel; Adji, Fajar Rachman; Shubham, Kumar (Sustainability (STPP) Theory, Practice and Policy, 2025)
This research examines how the ecotourism expansion in Fiji affects biodiversity conservation and Indigenous cultural heritage. The growth of ecotourism has led to major changes in the tourism sector. It significantly impacts the country's biodiversity conservation and indigenous cultural heritage. This research used a literature review approach, collecting and analyzing secondary data from various relevant sources at each stage of the research. The findings reveal a complex interconnection between economic interests and cultural dynamics, shaping Fiji's ecotourism practices and management. While ecotourism initiatives have emphasized preserving the natural environment and the promotion of indigenous cultural heritage, concern has emerged regarding the negative impacts on the fragile ecosystem and the exploitation of cultural resources for commercial gain. This research provides valuable insights into the challenges and opportunities associated with ecotourism expansion in Fiji, ensuring sustainable development and the protection of biodiversity and cultural heritage.